Red Ring Nematode, Bursaphelenchus cocophilus (Cobb) Baujard (Nematoda: Secernentea: Tylenchida: Aphelenchina: Aphelenchoidea: Bursaphelechina) formerly Rhadinaphelenchus cocophilus - Angela S. Brammer; William T. Crow (EDIS)
Bursaphelenchus cocophilus causes red ring disease of palms. Symptoms of red ring disease were first described on Trinidad coconut palms in 1905. Red ring disease can appear in several species of tropical palms, including date, Canary Island date and Cuban royal, but is most common in oil and coconut palms. The red ring nematode parasitizes the palm weevil Rhynchophorus palmarum L., which is attracted to fresh trunk wounds and acts as a vector for B. cocophilus to uninfected trees. This document is EENY-236, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2001.